Predicting the unpredictable: General Aviation (GA) aircraft cost estimation evaluation. (July 2022) - Shahriar, Ali; Khandoker, Azad; Gessl, Guido; Sint, Sabine; Hamid, M.A.; Tariq, Abrar; Rahman, Al
Abstract: Cost estimation is an important part of project planning as well as research endeavor. Since the well-established cost estimation models used in the GA aircraft industry are already several decades old, a re-evaluation of their applicability to current market conditions is essential. Reliable cost estimation may also improve the chances to get external funding - a vital point for start-ups. To tackle this issue, we developed a research method to investigate potential cost models for GA aircraft that can serve as a guideline for, e.g., start-ups and research works. After gathering existing cost estimation models, they are classified and analyzed to find the ones most suitable for small aircraft. For evaluation purpose, the two most promising ones are applied to data from existing aircraft models to compare their accuracy and finally the best one is coded as an application in Python to improve usability. With our presented research method we show a possibility to perform early cost estimation for small GA aircraft and offer a software tool to simplify its application. Highlights: Proposal of a research process to explore and analyze different cost models. Investigation of various development cost models for General Aviation aircraft. Evaluation of two General Aviation aircraft development cost models using publicly available data. Implementation of our chosen development cost model for General Aviation aircraft (DAPCA IV) as a software tool.